Evaluation of anterior maxillar microstrain with bone regeneration. A finite element analysis - Aguilar Henao, Johan Ivan (2019)
Objetive. The purpose of this study was to know and determine the microstrain and stress distribution in bucal bone, regenerated and rehabilitated with an implant using the finite element analysis (FEA). Methods. The thickness of maxillar bone modeling with bucal bone regeneration was 1.5 mm with a dental implant in position of the central incisor (Cancellous, cortical and regenerated bone, implant and prosthetic components). The variables were the modulus of elasticity and Poisson`s ratio for all the components in the model. A load of 200 N was applied to the palatal surface of the crown in order to calculate the microstrain stress distribution of the bone. Results. The maximum equivalent stress values of von Mises were found in the cortical bone (44.89 MPa) surrounding the neck of the implant and concentrated on the first four implant threads adjacent to the native bone in the palatal area, with cortical bone, while in the regenerated bone, in the vestibular area, it was concentrated until thread six, decreasing stress (2.5 MPa), and bone microdeformation was greater in cortical bone (943 με) compared to native bone (214 με). Conclusions. The distribution of stresses and microstrain generated on the model, had different behavior depending on the type of bone (Cortical, cancellous, regenerated bone), the rigid cortical bone with bigger modulus of elasticity resisted more efforts and microstrain just like the implant that had a higher modulus of elasticiy and distributed less effort over the regenerated bone.